Some Actual Directions of Modernization of Russian Federation Legislation on Administrative Responsibility - Kononov, Pavel I. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article deals with the most urgent problems of improving the legal regulation of the institution of administrative responsibility. The author suggests new approaches to understanding the essence, purpose and principles of administrative responsibility in the current state of the state and society, and taking into account these approaches, specific proposals are made to clarify and supplement the General Part of the Code of the Russian Federation on Administrative Offenses.